La ampliación de la UE hacia el Este: análisis del proceso de convergencia con una perspectiva mundial - Delgado Rodríguez, Mª Jesús; Lucas Santos, Sonia De; Álvarez Ayuso, Inmaculada (Papeles de Europa, 2010)
This article analyzes the economic convergence in the countries of Central and Eastern Europe from a broad perspective, which will provide comparative evidence on the process of convergence for the different world regions. The extensive coverage of the database will make possible to assess the trajectory of the countries of Central and Eastern Europe before and after joining the EU. In this analysis we will apply the methodology of panel data in order to compare the results and expand the available evidence. The evidence shows that the European convergence process is maintained after the entry of the countries of Central and Eastern Europe in the European Union. Furthermore, it appears that this group of countries have managed to intensify the process of convergence in the period studied and this group of countries achieving one of the more favorable results among the world regions.